Recontextualizing responsibility for justice: the lynching trope, racialized temporalities, and cultivating breathable futures. Issue 2 (3rd April 2021) - Houdek, Matthew
ABSTRACT: This essay critically engages the Equal Justice Initiative's (EJI) Lynching in America report to illuminate how it uses lynching as a trope to gesture to an otherwise temporality of anti-Black violence that recontextualizes what it means to be responsible for structural injustice. Overall, through my analysis and by engaging theories of justice, racialization, and racialized time, while also centering the language of breathing and suffocation drawn from various Black voices, I advance a breathing-centered conception of responsibility for justice that is attuned to imagining a future beyond the enduring legacies of lynching.